One-back reinforcement dissociates implicit-procedural and explicit-declarative category learning. - Smith, J. David; Jamani, Sonia; Boomer, Joseph; Church, Barbara A. (Memory & Cognition, 2018)
The debate over unitary/multiple category-learning utilities is reminiscent of debates about multiple memory systems and unitary/dual codes in knowledge representation. In categorization, researchers continue to seek paradigms to dissociate explicit learning processes (yielding verbalizable rules) from implicit learning processes (yielding stimulus-response associations that remain outside awareness). We introduce a new dissociation here. Participants learned matched category tasks with a multidimensional, informationintegration solution or a one-dimensional, rule-based solution. They received reinforcement immediately (0-Back reinforcement) or after one intervening trial (1-Back reinforcement). Lagged reinforcement eliminated implicit, information-integration category learning but preserved explicit, rule-based learning. Moreover, information-integration learners facing lagged reinforcement spontaneously adopted explicit rule strategies that poorly suited their task. The results represent a strong process dissociation in categorization, broadening the range of empirical techniques for testing the multiple-process theoretical perspective. This and related methods that disable associative learning--fostering a transition to explicit-declarative cognition--could have broad utility in comparative, cognitive, and developmental science.